2004
DOI: 10.1002/jcp.20180
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane graft: Histopathological findings in five cases

Abstract: Amniotic membrane transplantation (AMT) is an effective treatment for ocular surface reconstruction; however, the mechanisms through which amniotic membrane (AM) exerts its effects as well as its fate after transplantation have not been entirely elucidated and have been investigated only in part. We evaluate the integration of AM in the host cornea in five patients who underwent AMT as the result of Bowen's disease, band keratopathy, radio- or cryotherapy-induced keratopathy, chemical burn or post-herpetic dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
0
20
1
Order By: Relevance
“…[16][17][18] We could not address this issue in our study. We presumed that even if amniotic membrane remnants were to remain on the cornea, their presence would be insufficient to prevent recurrence.…”
Section: Discussionmentioning
confidence: 60%
“…[16][17][18] We could not address this issue in our study. We presumed that even if amniotic membrane remnants were to remain on the cornea, their presence would be insufficient to prevent recurrence.…”
Section: Discussionmentioning
confidence: 60%
“…14 In infective corneal diseases, the transplantation of a multilayer amniotic membrane can increase the thickness of the corneal stroma and avoid complications such as ulcer perforation. [26][27][28][29][30] In this study, corneal OCT showed gradual thinning of the amniotic membrane in the 12 eyes with stable ocular surfaces. Discontinuity of the amniotic membrane was observed at 4 months after cultivated limbal epithelial transplantation and became more evident at 1 year.…”
Section: Amniotic Membrane Transplantation Can Play Amentioning
confidence: 86%
“…It was found that none of the eyes showed remnants of AM in the cornea, and Bowman membrane was disrupted in all cases. 19 The authors concluded that the efficacy of AMT was more through its biological properties than through its mechanical properties. 19 Complications that can occur after AMT include hematoma formation in the postoperative period, 20 granuloma formation, or premature degradation of the membrane requiring a repeat procedure.…”
Section: Discussionmentioning
confidence: 98%
“…In one study, 19 5 eyes that underwent AMT and subsequent penetrating keratoplasty or enucleation were subjected to histopathological analysis. It was found that none of the eyes showed remnants of AM in the cornea, and Bowman membrane was disrupted in all cases.…”
Section: Discussionmentioning
confidence: 99%